Use of a Zwitterionic Surfactant to Improve the Biofunctional Properties of Wool Dyed with an Onion (Allium cepa L.) Skin Extract - Chiara Puri; Lucia Pucciarini; Matteo Tiecco; Virginia Brighenti; Claudia Volpi; Marco Gargaro; Raimondo Germani; Federica Pellati; Roccaldo Sardella; Catia Clementi (MDPI AG, 2020)
To improve the loadability and antioxidant properties of wool impregnated with onion skin extract, the introduction of SB3-14 surfactant in the dyeing process was evaluated. A preliminary investigation on the surfactant-quercetin interaction indicated that the optimal conditions for dye solubility, stability, and surfactant affinity require double-distilled water (pH = 5.5) as a medium and SB3-14 in a concentration above the c.m.c. (2.5 × 10−3 M). The absorption profile of textiles showed the flavonoid absorption band (390 nm) and a bathochromic feature (510 nm), suggesting flavonoid aggregates. The higher absorbance for the sample dyed with SB3-14 indicated greater dye uptake, which was further confirmed by HPLC analysis. The Folin-Ciocalteu method was applied to evaluate the total phenol content (TPC) released from the treated wool, while the assays FRAP, DPPH, ABTS, and ORAC were applied to evaluate the corresponding total antioxidant activity (TAC). Higher TPCs (about 20%) and TACs (5-55%) were measured with SB3-14, highlighting textiles with improved biofunctional properties. Spectrophotometric analyses were also performed with an artificial sweat. The potential cytotoxic effect of SB3-14 in both monomeric and aggregated forms, cell viability, and induction of apoptosis were evaluated in RAW 264.7 cells. These analyses revealed that SB3-14 is safe at concentrations below the c.m.c.